The characterization of weak protein-protein interactions: evidence from DEER for the trimerization of a von Willebrand Factor A domain in solution. - Banham, J; Timmel, C; Abbott, R; Lea, S; Jeschke, G (2006)
(Figure Presented) Distance determination: A double electron electron resonance (DEER) measurement of a distance of 6.1 nm (green lines) between singly nitroxide-labeled human von Willebrand Factor A domains demonstrates oligomerization of this domain in dilute solution (see structure); probably in an arrangement similar to that observed in the crystal structure. The DEER technique should be generally applicable for characterizing noncovalent interactions between macromolecules in solution. © 2006 Wiley-VCH Verlag GmbH and Co. KGaA.